2010
DOI: 10.1111/j.1099-0860.2010.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Concerns about their Parents’ Health and Well‐being: Researching with ChildLine Scotland

Abstract: This paper reports on collaborative research conducted with ChildLine Scotland, a free, confidential, telephone counselling service, using their database. We focussed on children’s calls about parental health and well‐being and how this affected their own lives. Children’s concerns emerged within multi‐layered calls in which they discussed multiple issues and problems in their lives such as alcohol misuse, drug misuse, domestic violence, family relationships, depression, mental health problems and bereavement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The parenting of these pupils is frequently negatively appraised and viewed as deficient, with their children's socio-emotional difficulties blamed on a lack of parental responsibility (Gill & Liamputtong, 2009;Francis, 2012), yet the implications of this for ensuring pupils' socio-emotional needs are addressed has not been thoroughly considered. Additionally, although there are suggestions that pupils may not disclose their home problems with authority figures such as educational practitioners (Backett-Milburn & Jackson, 2012), those employed in many BESD schools are in a unique position. This is because class sizes are usually smaller than the mainstream norm, enabling practitioners to form strong, trusting relationships with their pupils, with the possibility of encouraging pupils to share their socio-emotional difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…The parenting of these pupils is frequently negatively appraised and viewed as deficient, with their children's socio-emotional difficulties blamed on a lack of parental responsibility (Gill & Liamputtong, 2009;Francis, 2012), yet the implications of this for ensuring pupils' socio-emotional needs are addressed has not been thoroughly considered. Additionally, although there are suggestions that pupils may not disclose their home problems with authority figures such as educational practitioners (Backett-Milburn & Jackson, 2012), those employed in many BESD schools are in a unique position. This is because class sizes are usually smaller than the mainstream norm, enabling practitioners to form strong, trusting relationships with their pupils, with the possibility of encouraging pupils to share their socio-emotional difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…The children supported these ideas, suggesting that death be taught within the curriculum and spoken about when someone dies. This focus supports the creation of an environment where experiences of death and bereavement can be shared with peers and adults: the significance of which is recognised across a range of health and well‐being issues (Backett‐Milburn and Jackson, ). Such developments might serve to address death illiteracy, which, in turn, might renegotiate ambivalence.…”
Section: Discussion: Conceptualising Death Ambivalencementioning
confidence: 90%
“…Previous research has demonstrated that direct social control efforts from social networks that include adult children promote the healthy behavior of adults in later life; however, this work has not isolated adult children from other network members and thus cannot determine the specific processes that characterize children's direct social control efforts (Laroche & Snetselaar, ; Tucker et al, ; Williams, ). It is also plausible that school‐age children attempt to regulate their parents' diet and exercise habits as they become more aware of healthy behavior norms through school, media sources, and parents themselves (Backett‐Milburn & Harden, ; Backett‐Milburn & Jackson, ).…”
Section: Introductionmentioning
confidence: 99%